IMPLEMENTING TASK-BASED INSTRUCTION AND GENRE-BASED APPROACHES TO DEVELOP STUDENTS WRITING SKILLS - Sodiqova Moxirabonu Baxromovna (Western European Studies, 2024)
This paper explores the integration of task-based instruction (TBI) and a genrebased approach (GBA) to develop students' writing skills comprehensively. TBI emphasizes real-world tasks to stimulate authentic writing experiences, while GBA focuses on genre conventions and rhetorical structures. The integration of these approaches offers a holistic strategy for enhancing students' writing proficiency, genre awareness, and communicative competence. Through an analysis of theoretical frameworks, practical applications, and empirical evidence, this study highlights the benefits of combining TBI and GBA in writing instruction. The findings suggest that the integrated approach fosters improved writing outcomes, increased student motivation and engagement, effective collaboration and feedback mechanisms, and transferable writing skills applicable to diverse contexts. The paper concludes with recommendations for educators to optimize writing instruction using TBI and GBA strategies.
Keywords: Writing proficiency; discourse communities; explicit instruction